A novel synthesis of ZnO/N-doped reduced graphene oxide composite as superior anode material for lithium-ion batteries. (February 2016) - Dai, Juan; Wang, Min; Song, Ming; Li, Pengcheng; Zhang, Chunyan; Xie, Anjian; Shen, Yuhua
Abstract: A ZnO/N-doped reduced graphene oxide (N-doped GN) composite was synthesized by a pressure-adjusted hydrothermal in ammonia atmosphere. When used as an anode material for lithium ion batteries (LIBs), the ZnO/N-doped GN-3 prepared at 1 MPa, which contains 8.7% N, achieved an ultrahigh reversible capacity of 1100 mA h g − 1 after 100 cycles at a current density of 0.2 A g − 1 that exceeds the theoretical capacity (978 mA h g − 1 ) of ZnO and previous related highest value (900 mA h g − 1 at 0.1 A g − 1 ), which made it a promising anode material for LIBs. Graphical abstract: A ZnO/N-doped-GN composite was synthesized via a high-pressure hydrothermal in ammonia atmosphere, more importantly it exhibits excellent lithium storage. ZnO NPs of less than 50 nm were uniformly anchored on the matrix of N-doped GN to form the ZnO/N-doped-GN composite. Such an architecture established by GN sheets could efficiently enhance the conductivity of the electrode and buffer the volume expansion of ZnO NPs during insertion–extraction of lithium-ions, and ensure favorable transport kinetics for both electrons and lithium ions. The ZnO/N-doped-GN-3 composite shows superb cycling stability and rate capability when used as an anode for LIBs. It can maintain a high reversible capacity of 1100 mA h g − 1 after 100 cycles at 0.2 A g − 1, higher than the theoretical capacity of ZnO (978 mA h g − 1 ), which so far has been proved to be the best among all ZnO-graphene based electrode materials. Additionally, the current synthesis strategy is low-cost and effective and it may be extended to prepare other various functional composite nanomaterials, which have wide applications in catalysis and electrochemical areas.